Reasons behind non-adherence of healthcare practitioners to pediatric asthma guidelines in an emergency department in Saudi Arabia - Wahabi Hayfaa A; Alziedan Rasmieh A (BMC, 2012)
Abstract Background The prevalence of childhood bronchial asthma in Saudi Arabia has increased in less than a decade from 8% to 23%. Innovations in the management of asthma led to the development of evidence based clinical practice guidelines and protocols to improve the patients' outcomes. The objectives of this study are to examine the compliance of the healthcare providers in the Pediatrics Emergency Department, in King Khalid University Hospital, with the recommendations of the Pediatrics Asthma Management Protocol (PAMP), and to explore the reasons behind non-adherence. Methods This study is designed in 2 parts, a patients' chart review and a focus group interview. The medical records of all the children who presented to the Pediatric Emergency Department (PED) and were diagnosed as asthmatic, during the period from the 1st of January 2009 to the 31st of March 2009, were reviewed to investigate the compliance of healthcare providers (physicians and nurses) with 8 recommendations of the PAMP which are considered to be frequently encountered evidence-practice gaps, and these are 1) documentation of asthma severity grading by the treating physician and nurse 2) limiting the prescription of Ipratropium for children with severe asthma 3) administration of Salbutamol through an inhaler and a spacer 4) documentation of parental education 5) prescription of systemic corticosteroids to all cases of acute asthma 6) limiting chest x-ray requisition for children with suspected chest infection 7) management of all cases of asthma as outpatients, unless diagnosed as severe or life threatening asthma 8) limiting prescription of antibiotics to children with chest infection. The second part of this study is a focus group interview designed to elicit the reasons behind non- adherence to the recommendations detected by the chart review. Two separate focus group interviews were conducted for 10 physicians and 10 nurses. The focus group interviews were tape-recorded and transcribed verbatim. Theory-based content analysis was used to analyze interviews into themes and sub-themes. Results and discussion A total of 657 charts were reviewed. The percentage of adherence by the healthcare providers to the 8 previously mentioned recommendations was established. There was non-adherence to the first 5 of the 8 aforementioned recommendations. Analysis of the focus group interview revealed 3 main themes as reasons behind non-compliance to the 5 recommendations mentioned above and those are 1) factors related to the organization, 2) factors related to the asthma management protocol 3) factors related to healthcare providers. Conclusion The organizational barriers and the lack of an implementation strategy for the protocol, in addition to the attitude and beliefs of the healthcare providers, are the main factors behind non-compliance to the PAMP recommendations.